Jewish national decline and biblical figures as classical exempla: Moses, Aaron, Joshua, David, and Elisha in De Excidio 5.2.1 - Bay, Carson (Journal of the bible and its reception, 2020)
The fourth century of the Common Era was a period significant for witnessing the effective birth of Christian historiography and the (putatively) definitive separation of ‘Jew’ and ‘Christian’ as distinctive identities. A text emerged, known as Pseudo-Hegesippus or De Excidio Hierosolymitano (On the Destruction of Jerusalem). This text illustrates how Christian historiography and Christian anti-Jewish ideology at that time could engage with the traditions of classical antiquity. In particular, this article argues that Pseudo-Hegesippus deploys figures from the Hebrew Bible in the mode of classical exempla and that it does so within the largely classical conceptual framework of national decline. For Pseudo-Hegesippus, biblical figures presented as classical exempla serve to illustrate the historical decline of the Jews until their effective end in 70 CE (when the Romans destroyed Jerusalem and the Temple). One passage, De Excidio 5.2.1, and its enlistment of five Hebrew heroes illustrates this point particularly well. The use of exemplarity and the theme of national decline employed there help us appreciate De Excidio as a distinctive contribution to early Christian historiography and anti-Jewish literature in late antiquity; this expands our ability to imagine the ways in which fourth-century Christian authors could conceive of and articulate Jewish history in classical terms.